Methodology for DSC calibration in high heating rates - Braga, Carlos Isidoro; Rezende, Mirabel Cerqueira; Costa, Michelle Leali [UNESP] (FapUNIFESP (SciELO), 2011)
Despite the large use of differential scanning calorimetry (DSC) technique in advanced polymer materials characterization, the new methodology called DSC in high heating rates was developed. The heating rate during conventional DSC experiments varying from 10 to 20°C.min-1, sample mass from 10 to 15mg and standard aluminum sample pan weighting, approximately, 27mg. In order to contribute to a better comprehension of DSC behavior in different heating rates, this work correlates as high heating rate influences to the thermal events in DSC experiments. Samples of metallic standard (In, Pb, Sn and Zn) with masses varying from 0.570mg to 20.9mg were analyzed in multiples sample heating rate from 4 to 324°C. min-1. In order to make properly all those experiments, a precise and careful temperature and enthalpy calibrations were performed and deeply discussed. Thus, this work shows a DSC methodology able to generate good and reliable results on experiments under any researcher choice heating rates to characterize the advanced materials used, for example, for aerospace industry. Also it helps the DSC users to find in their available instruments, already installed, a better and more accurate DSC test results, improving in just one shot the analysis sensitivity and resolution. Polypropylene melting and enthalpy thermal events are also studied using both the conventional DSC method and high heating rate method.
Keywords: Calibration; DSC; High heating rate; Polymers; Thermal analysis; Advanced materials; Advanced polymers; Enthalpy calibration; High heating rates; Sample heating; Thermal events; Aerospace industry; Characterization; Differential scanning calorimetry; Enthalpy; Experiments; Heating rate; Lead; Polypropylenes; Sensitivity analysis; Thermoanalysis; Tin; Heating